A Robust Route to Co2(OH)2CO3 Ultrathin Nanosheets with Superior Lithium Storage Capability Templated by Aspartic Acid‐Functionalized Graphene Oxide. Issue 26 (27th May 2019) - Zhao, Shiqiang; Wang, Zewei; He, Yanjie; Jiang, Hongrui; Harn, Yeu Wei; Liu, Xueqin; Su, Chenliang; Jin, Huile; Li, Ying; Wang, Shun; Shen, Qiang; Lin, Zhiqun
Abstract: Two‐dimensional (2D) nanomaterials are widely recognized as an important class of functional materials possessing superior electrochemical reaction kinetics. Herein, an L ‐aspartic acid (AA)‐modified graphene oxide (GO) templating strategy is developed to in situ yield ultrathin (i.e., ≈5 nm) cobalt carbonate hydroxide (Co2 (OH)2 CO3 ) nanosheets as advanced anode materials of lithium ion batteries. Notably, the covalent tethering of AA on the GO surface renders a high density of carboxyl groups that impart effective loading of Co‐containing precursors and subsequent growth into Co2 (OH)2 CO3 nanosheets bridging adjacent GO layers. The lasagna‐like Co2 (OH)2 CO3 ‐GO nanocomposites exhibit an ultrahigh lithium storage capacity of 1770 mAh g −1 after 500 cycles at 100 mA g −1 . It is noteworthy that the cycled Co2 (OH)2 CO3 phase separates into homogeneously dispersed Co(OH)2 and CoCO3 phases with two different charge plateaus at ≈1.2 and 2.0 V, respectively, which effectively inhibit large‐scale homophase coarsening of Co, Li2 CO3, and LiOH. The much shortened Li + /e − transfer distance enabled by individual ultrathin Co2 (OH)2 CO3 nanosheet together with robust layer‐by‐layer assembled nanostructure of Co2 (OH)2 CO3 ‐GO confers the superior electrochemical reactivity and mechanical stability. As such, the amino acid‐modified GO templating strategy may represent a simple yet robust means of crafting a variety of 2D nanostructured composites of interest for energy storage applications. Abstract : Ultrathin Co2 (OH)2 CO3 nanosheets uniformly encapsulated within graphene matrixes are crafted via an aspartic acid‐functionalized graphene oxide templating strategy. The short Li + /e − transfer distance, fast electron transmission, robust lasagna‐like assemblies, and synergistic effect of conversion reactions in dispersed yet adjacent Co(OH)2 phase and CoCO3 phase render ultrahigh lithium storage capacity of 1770 mAh g −1 and outstanding cycling and rate performance.